STRATEGI LAYANAN DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA DENPASAR PADA MASA PANDEMI COVID-19 - Meysi Anggiyani, Ni Kadek; Haryanti, Ni Putu Premierita; Suhartika, I Putu (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2022)
The Covid-19 pandemic that hit Indonesia has hampered people's daily activities. Libraries as institutions that provide services to the community are also affected. A very influential impact is the implementation of services that do not run optimally. The purpose of this study was to determine the service strategy of the Denpasar City Library and Archives Service during the Covid-19 pandemic. This study uses a descriptive type of research with a qualitative approach. Data collection techniques through observation, interviews with service librarians and users at the Denpasar City Library and Archives Service, and documentation. The object of this research is the service strategy of the Denpasar City Library and Archives Service. This research was conducted for 2 months, namely March – May 2022. The results of this study are expected to be able to provide maximum service to users as before the Covid-19 pandemic. Keywords : library services, digital services, library promotion, Denpasar city library and archives service, covid-19